2010
DOI: 10.1089/vim.2009.0095
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anti-HCV Antibodies in IL-10-Treated Patients

Abstract: There is limited information on the direct role of the neutralizing antibody responses against hepatitis C virus (HCV) infection or methodologies to study them. Previously we have demonstrated that interleukin-10 (IL-10) administered to chronic hepatitis patients led to a decrease in disease activity, but an increase in HCV viral burden. The mechanism behind this is unknown. The objective of this study was to examine the antibody response in IL-10-treated patients. To establish a neutralization antibody assay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The potent anti‐inflammatory properties of IL‐10 made it appealing to study its therapeutic implications in various human diseases. These include the following: psoriasis [129], wound healing [130], rheumatoid arthritis [131], sepsis [132,133], organ transplantation [134,135], visceral and limb ischaemia [136], atherosclerosis [137], chronic Hepatitis C [138,139], HIV infection [140], post‐ERCP pancreatitis [141], coeliac disease [142] and IBDs [143], especially CD. The first therapeutic administration of recombinant human IL‐10 (rhuIL‐10) back in the mid‐1990s raised hope for a potential treatment option in CD [144].…”
Section: Therapeutic Implications Of Il‐10 In Ibdmentioning
confidence: 99%
“…The potent anti‐inflammatory properties of IL‐10 made it appealing to study its therapeutic implications in various human diseases. These include the following: psoriasis [129], wound healing [130], rheumatoid arthritis [131], sepsis [132,133], organ transplantation [134,135], visceral and limb ischaemia [136], atherosclerosis [137], chronic Hepatitis C [138,139], HIV infection [140], post‐ERCP pancreatitis [141], coeliac disease [142] and IBDs [143], especially CD. The first therapeutic administration of recombinant human IL‐10 (rhuIL‐10) back in the mid‐1990s raised hope for a potential treatment option in CD [144].…”
Section: Therapeutic Implications Of Il‐10 In Ibdmentioning
confidence: 99%
“…The establishment of a cell-culture system for HCV has allowed evaluation of antibodies that can neutralise HCV infection. Neutralising antibody (nAb) can be detected using the HCV genotype 2a strain, JFH-1, in HCV mono-infected patients chronically infected with different HCV genotype [11,12]. HIV co-infection reduced nAb levels in a cross-sectional study [13], but we have found no longitudinal data examining HIV/HCV patients after starting ART.…”
Section: Introductionmentioning
confidence: 77%